Digital age: The importance of 21st century skills among the undergraduates - Mahmud, Malissa Maria; Wong, Shiau Foong (Frontiers in Education, 2022)
The recent emphasis on refining the quality of higher education has incited insightful debates about numerous education reforms. Due to the demands of our ever-changing world, many institutions have begun to embed 21st century skills into the curriculum design to better prepare the students for workplace success and lifelong career development. Despite its importance, there are disparities in regards to establishing an in-depth understanding of its significance. Thus, this study is aimed to investigate the perspective of undergraduate students in Malaysia on the importance of 21st century skills for career readiness. The findings assert that data literacy is an essential skill to excel in the workplace, and similarly, problem-solving skill helps develop critical thinking skill, which contribute to the development of creative thinking skill. Recommendations are further deliberated.